Identification and characterizations of a rhoptries neck protein 5 (BoRON5) in Babesia orientalis. (August 2020) - Tian, Yu; Li, Fangjie; Guo, Jiaying; Hu, Yanli; Shu, Xiang; Xia, Yinjun; Kang, Ting; Yu, Long; Liu, Qin; Nie, Zheng; Wang, Sen; Ao, Yangsiqi; et al.
Abstract: Babesiosis caused by Babesia orientalis is one of the most serious parasitic diseases of water buffalo in the central and south part of China. Rhoptry neck proteins (RONs) are very important protein components to form a complex moving junction (MJ) which mainly participate in the invasion processes in apicomplexan parasites. Aimed to the further investigation of the function of Bo RON proteins in B. orientalis, in this study, Bo RON5 was characterized. A truncated 921 bp fragment of Bo RON5 with predicted antigenic epitopes was cloned and inserted into pSUMO expression vector. Recombinant protein rSUMO- Bo RON5 was purified from Escherichia coli . and used to produce antisera in Kunming mice. rSUMO- Bo RON5 showed strong immunosignals when blotted with the positive serum from B. orientalis -infected water buffalo. Antisera raised in Kunming mice against rSUMO- Bo RON5 could detect the native Bo RON5 in parasite lysates. Immuofluorescence assay showed that 谈何 mice antisera of rSUMO- Bo RON5 could detect merozoite in B. orientalis infected water buffalo erythrocytes. This study provides useful information for the further investigation of the Bo RON5 function during B. orientalis invasion of water buffalo. Highlights: B. orientalis Bo RON5 was characterized. Bo RON5 shares 6 conserved cysteine residues with 5 putative RON5 from Babesia sp. Bo RON5 contains a SP and a predicted TM. Antisera raised in mice against recombinant Bo RON5 possess antigenicity feature.